Víctor F. S. Sit (editor). Chinese cities: the growth of the metropolis since 1949. Oxford, Nueva York : Oxford University Press, 1985. 239 p. - Schteingart, Martha (Estudios Demográficos y Urbanos, 1986)
VÍCTOR F.S. SIT (editor). Chínese Cities. The Growth of the Metropolis since 1949. Oxford University Press, Oxford, Nueva York, Hong Kong, 1985.